(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The international organizations (OIE, WHO and European Commission) have promoted the use of serological testing in addition to other specific requirements as an alternative to the quarantine for free movements of pets in certain countries. They have also recommended that countries involved in oral vaccination programmes against rabies should monitor the efficacy of the campaigns by testing a certain number of field samples collected from the target species to check their immunity against rabies. The WHO/OIE reference tests (the FAVN test and the RFFIT) are time-consuming, expensive, require highly-trained technicians, the maintenance of cell cultures, laboratories with a high containment level and vaccinated technicians to handle live rabies virus. In addition, since they are based on cell cultures, they are sensitive to any cytotoxic products and contaminating agents present in samples. We have evaluated the performances of a commercial ELISA (BioPro Rabies ELISA Ab kit, Czech Republic), a blocking ELISA that detects rabies virus antibodies, in reference to the FAVN test. The specificity assessed on 315 samples from unvaccinated dogs and cats was 100%. A total of 701 samples from vaccinated dogs and cats were tested using the FAVN test and the ELISA. The overall agreement between the two tests was found equal to 86%. Considering samples from wildlife, a total of 188 sera from foxes and raccoon dogs were sampled in a rabies-free country. The specificity reached 100% in those sera taken from naïve animals. Overall, a high concordance (95%: 648 out of 682 sera) was observed between the BioPro ELISA and the FAVN test, which was similar in sera from red foxes (95.1%: 388 out of 408 sera) and raccoon dogs (94.9%: 260 out of 274 sera). The concordance between tetracycline and seropositivity results was also evaluated. The overall agreement with tetracycline results was excellent in the fox for both the BioPro ELISA (95.9%) and the FAVN test (91.8%). Concordance was slightly lower in the raccoon dog, with a value of 82.8% for the BioPro ELISA and 78.4% for the FAVN test. Rabies antibodies were equally detected with the BioPro ELISA in animals vaccinated with different types of vaccines (SAG2 or VRG vaccine baits) and in highly haemolysed sera. In our hands, the BioPro ELISA is a valuable alternative to the FAVN test for assessing rabies antibody titres in vaccinated pets and in fox and raccoon dog populations for the follow up of oral vaccination campaigns efficacy. An inter laboratory collaborative study is planned in the next future to assess the reproducibility of the BioPro ELISA for laboratories involved in the monitoring of oral vaccination programmes.